Ethnicity, Race, Religion Identities and Ideologies in Early Jewish and Christian Texts, and in Modern Biblical Interpretation - Hockey, Katherine M.; Horrell, David (Bloomsbury Academic, 2018)
Religion, ethnicity and race are facets of identity that have become increasingly contested. The modern discipline of biblical studies developed in the context of Western Europe, concurrent with the emergence of various racial and imperial ideologies. The essays in this volume deal both with historical facets of ethnicity and race in antiquity, in particular in relation to the identities of Jews and Christians, and also with the critique of scholarly ideologies and racial assumptions which have shaped biblical studies.